How does gender moderate customer intention of shopping via live-streaming apps during the COVID-19 pandemic lockdown period? - Zhao, Yuyang (2021)
Zhao, Y., & Bacao, F. (2021). How does gender moderate customer intention of shopping via live-streaming apps during the COVID-19 pandemic lockdown period? International Journal of Environmental Research and Public Health, 18(24), 1-24. [13004]. https://doi.org/10.3390/ijerph182413004